An investigation on oral communication apprehension in classrooms among final year undergraduates of electrical engineering in UiTM / Nik Nurul Ain Nik Ab Kadir - Nik Ab Kadir, Nik Nurul Ain (2014)
English is widely used and becomes the means of communication for most countries in the recent years. In Malaysia, English language has become the second language used after the official language, Bahasa Malaysia. The need for English oral communication skills is seen in working disciplines and engineering is not exceptional. However, communication apprehension could be the hindrance for fresh graduates especially when employers highlight on good English oral communication skills as on of the criteria for employment. Communication apprehension among final year undergraduates is a worthy of investigation because it is a factors that affects communicative competence. Specifically, the study examines 1) the level of communication apprehension (CA) among final year students of Electrical Engineering (EE), 2) how EE students participate in the classroom, 3) the techniques used by lecturers in classroom oral activities, 4) EE students’ opinions on the techniques used by lecturers in oral classroom activities and 5) EE students’ preferred techniques used by lecturers in classroom oral activities. Data for this study is obtained through an interview and a survey questionnaire administered to 60 final year undergraduates of EE in UiTM Shah Alam. Findings suggest that most of the students experience average level of communication apprehension. In oral classroom activities, there are several techniques used by lecturers to encourage the students to participate. However, the students have their own preferences on the techniques used by lecturers in oral classroom activities. Thus, lecturers must learn to identify appropriate techniques that fit students’ preferences and be able to reduce students’ communication apprehension. In this way, the teacher will have the awareness about the learning process of the oral skills defined along the construct of communication apprehension.